The Correlation between Family Communication, Environment, and Instagram with Adolescent Delinquency Behavior: Korelasi Komunikasi Keluarga, Lingkungan, dan Instagram dengan Perilaku Kenakalan Remaja - Kurniawan, Bima Dwi; Rochmaniah, Ainur (House of Wisdom: Journal on Library and Information Sciences, 2025)
General Background: In the current era, adolescent character is significantly shaped by surrounding factors, including family, environment, and social media. Specific Background: This study focuses on understanding the specific influence of these factors on the behavior of adolescents within the Indorunners community. Knowledge Gap: While the individual effects of these variables have been studied, there is a gap in research that simultaneously analyzes the combined and separate influences of family communication, environment, and Instagram on juvenile delinquency. Aims: This research, using a quantitative approach with a sample of 100 adolescents, aims to determine the effect of family communication, environment, and Instagram media on juvenile delinquency behavior. Results: The findings indicate that family communication, environment, and Instagram each have a partial and simultaneous influence on juvenile delinquency. The adjusted R-squared value of 44.3% demonstrates the combined contribution of these variables, with a strong correlation coefficient of 0.678. Novelty: The study's novelty lies in its specific analysis of the simultaneous influence of these three distinct factors on adolescent behavior within this particular community. Implications: The results suggest that effective family communication, a positive environment, and responsible use of Instagram are crucial for preventing juvenile delinquency. Highlights : Multiple Influences: The study found that family communication, environment, and Instagram all have a significant partial and simultaneous influence on juvenile delinquency. Quantitative Analysis: This research used a quantitative approach with a sample of 100 adolescents to analyze the relationships between the variables. Strong Correlation: The results show a strong correlation between the independent variables (family communication, environment, and Instagram) and the dependent variable (juvenile delinquency), with an adjusted R-squared of 44.3%. Keywords : Family Communication, Environment, Instagram, Juvenile Delinquency, Indorunners